Hubungan Kadar Gula Darah Dengan Tingkat Depresi Dan Aktifitas Fisik Pada Penderita Diabetes Mellitus Di Puskesmas Gatak Sukoharjo - MUJABI, M. FAIQ, Wachidah Yuniartika, S.Kep., Ns (2017)
High blood sugar levels will cause the occurrence of hyperglycemia. Hyperglycemia occurs because to an impaired insulin secretion or insulin work breakdown. People who hyperglycemia can experience interference in the form of phychological depression and decreased physical activity. People who are depressed and less activity can cause an increase in blood sugar levels. This research is a descriptive study using correlative approach cross sectional aims to do know the relationship between the blood sugar levels with the levels of depression and physical activity in people with Diabetes Mellitus in Sukoharjo Gatak Clinics. Sampling technique using a purpose sampling, while the research instrument using the BDI-II questionnaire of 21 items and IPAQ questionnaire.DAFTAR PUSTAKA Almatsier, Sunita. (2003). Prinsip dasar Ilmu Gizi. Jakarta : PT Gramedia Pustaka Utama American Diabetes Association. (2015). Diagnosis and Classification of Diabetes Mellitus. Diabetes Care Anani, S. (2012). Hubungan Antara Perilaku Pengendalian Diabetes dan Kadar Gula Darah Pasien rawat Jalan Diabetes Mellitus (Studi Kasus di RSUD Arjawinangun Kab Cirebon). Jurnal Kesehatan Masyarakat. 1: 466-478 Arief M.T.Q. (2008). Pengantar Metodologi Penelitian Untuk Ilmu Kesehatan cetakan 1. Surakarta : LPP UNS dan UNS Press Arikunto, S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik Edisi Revisi 2010. Jakarta : Rineka Cipta Aryani, Budi Ratna. 2011. Prevalensi Depresi Dan Hubungannya Dengan Nilai HbA1C Pada Pasien Pria Dengan Diabetes Mellitus Di RSUP Sanglah Denpasar. Universitas Udayana. Bertalina & Purnama. (2016). Hubungan Lama sakit, Pengetahuan, Motivasi Pasien dan Dukungan Keluarga dengan kepatuhan diet pasien diabetes mellitus. Jurusan Gizi Poltekkes Tajungkarang Black & Hawks. (2009). Medical Surgical Nursing Clinical Mnagement for Positive Outcomes. elseveir Saunders Bustan. (2007). Kualitas Hidup Pasien Diabetes Mellitus Tipe 2 Di Poli Interna RSD Dr. Soebandi Jember. Ciechanowski, P.S, Katon, W.Y, Russo, J.E. (2000). Impact of Depression on adherence, Function, adn Cost, Arch Intern Medd, 160: 3278-3285 Cholifah, dkk. (2015). Peran Faktor-faktor Psikologis Terhadap Depresi Pada Pasien Diabetes Mellitus Tipe 2 Vol. 41 No.1. UGM. Deuschle, Michael. (2013). Effects of antidepressants on glucose metabolism and diabetes mellitus type 2 in adults. Central Institute of Mental Health, University of Heidelberg, Medical Faculty Mannheim, Germany Depkes. (2008). Pengertian Diabetes Mellitus. Departemen Kesehatan RI Dinkes, Jateng. (2013). Profil Kesehatan Provinsi Jawa Tengah 2011. Semarang: Dinkes Provinsi Jateng Dinkes Sukoharjo. (2016). Studi Pendahuluan di Dinas Kesehatan Sukoharjo. Puskesmas Gatak. (2016). Studi Pendahuluan di Puskesmas Gatak Sukoharjo. Eko, A. (2010). Hubungan Aktifitas Fisik dan Istirahat dengan Kadar Gula Darah Pasien diabetes mellitus Rawat jalan RSUD Prof. Dr. Margono Soekardjo. Purwokerto : PSIK Universitas Muhammadiyah Purwokerto Eom, Young Sil; Park, Hwa Sun; Kim, Sei-Hyun; Yang, Sun Mee; Nam, Moon Suk; Lee, Hyoung Woo; Lee, Ki Young; Lee, Sihoon; Kim, Yeun Sun; Park, Ie Byung. (2011). Evaluation of Stress in Korean Clientss with Diabetes Mellitus Using the Problem Areas in Diabetes-Korea Questionnaire. Diabetes & Metabolisme, Volume 35, pp. 182-187. Fatmawati, Ari. (2013). Hubungan Tingkat depresi dengan Kualitas Hidup pada Pasien Diabetes Mellitus tipe 2 di Rumah sakit Islam Surakarta. Surakarta : UMS Ganong, F.W. (2009). Buku Ajar Fisiologi Kedokteran. Edisi 22. Jakarta : EGC Harikedua, V.T, Tando, N.M. (2012). Aktifitas Fisik dan Pola Makan dengan Obesitas Sentral pada tokoh Agama di Kota Manado. GIZIDO. 4:289-298 IDF. (2015). IDF Diabetes Atlas Sixth Edition Update, International Diabetes federation 2014. Ilyas, S. (2011). Ilmu Penyakit Dalam. Edisi ke 4. Jakarta : FK UI Irawan, Dedi. (2010). Prevalensi dan Faktor Risiko Kejadian Diabetes Melitus Tipe 2 di Daerah Urban Indonesia (Analisa Data Sekunder Riskesdas 2007). Thesis Universitas Indonesia. Isworo A., Saryono., (2010). Hubungan depresi dan Keluarga Terhadap Kadar Gula Darah Pada Pasien diabetes Mellitus Tipe 2. The Soedirman Journal Of Nursing. 5:37-44 Jelantik. (2014). Hubungan faktor Resiko Umur, Jenis kelamin, Kegemukan, dan Hipertensi dengan kejadian DM tipe II Di Wilayah Kerja Puskesmas Mataram. Universitas Mataram Kalache, A & Padnya, SM. (2002). Health Promotion and Aging. Di dalam Ratnaike RN (ed), Practical Guide to Geriatric Medicine. New York : McGraw-Hill Kaplan & Saddock. (2007). Synopsis of Psychiatry Behavioral Sciences and Clinical Psychiciatry. Philadelphia: Lippincot Williams and Willkins Karim, Faizati. (2006). Panduan Kesehatan Olahraga Bagi petugas kesehatan. Jakarta : Departemen Kessehatan Kekenusa. (2013). Hubungan antara Umur dan Riwayat keluarga Menderita DM dengan Kejadian Penyakit DM Tipe 2 pada Penderita Rawat jalan di Poliklinik Penyakit Dalam BLU RSUD Prof. Dr. R.D. Kandau Manado. Universitas Manado Kekenusa. (2013). Hubungan antara Umur dan Riwayat keluarga Menderita DM dengan Kejadian Penyakit DM Tipe 2 pada Penderita Rawat jalan di Poliklinik Penyakit Dalam BLU RSUD Prof. Dr. R.D. Kandau Manado. Universitas Manado Lubis, Namora Lumongga. (2009). Depresi Tinjauan Psikologis. Jakarta: Kencana Prenada Media Group. Mahanani, dkk. 2015. Aktifitas Fisik Berdasarkan Teori Handerson Pada Pasien Diabetes Mellitus Laki-laki Dan Perempuan. Stikes Rs Baptis Kediri. Misnadiarly. (2006). Diabetes Melitus Gangren, Ulcer, Infeksi, Mengenali gejala, Menanggulangi, dan Mencegah komplikasi. Jakarta: Pustaka Obor Populer. Murray, R.K. et al. (2003). Biokimia Harper. Edisi 25. Jakarta : EGC. National Institute of Mental Health. (2010). Depression and College Students, NIMH, 1-8. Nevid, J. S., et al. (2005). Psikologi Abnormal (Edisi Kelima). Jakarta: Erlangga. Nindyasari, N. (2010). Perbedaan Tingkat Kecemasan Pada Penderita Diabetes Mellitus (DM) Tipe I dengan Diabetes Mellitus (DM) Tipe II. Universitas Sebelas Maret Surakarta. Nobel, et al. (2005). Psikologi Abnormal (Edisi Kelima). Jakarta: Erlangga. Notoatmodjo, S. (2010). Metodologi Penelitian Kesehatan. Jakarta : Rineka Cipta Nurmalina, Rina. (2011). Pencegahan dan Menejemen Obesitas. Bandung : Elex Nursalam. (2008). Konsep dan Penerapan Metodologi Penelitian Ilmu Keperawatan. Jakarta : Salemba Medika Paramitha, Gumilang Mega. 2014. Hubungan Aktifitas Fisik Dengan Kadar Gula Darah Pada Pasien Diabetes Mellitus Tipe 2 Di Rumah Sakit Umum Daerah Karanganyar. FK UMS. Piette JD., Richardson C., Valenstein M. (2010). Depression In The Workplace. American Journal of Managed Care Potter and Perry. (2010). Buku Ajar Fundamental Keperawatan : Konsep, Proses, dan Praktik. Edisi 4.Volume 2.Alih Bahasa : Renata Komalasari, dkk. Jakarta: EGC. Powers, A.C. (2010). Diabetes Mellitus In: Jamerson J.L Harrison Endocrinology Ed 2. USA : McGraw-Hill Companies, Inc. 267-313 Price, A. S., & Wilson, L. M. (2005). Patofisiologi : Konsep Klinis Proses- proses Penyakit (Vol. 2). Jakarta: EGC. Purwaningsih, W dan Ina Karlina. (2012). Asuhan Keperawatan Jiwa. Cetakan II. Yogyakarta : Nuha Medika. Quirk et al. (2014). Systematic Review or Meta-analysis Physical activity interventions in children and young people with Type 1 diabetes mellitus: a systematic review with meta-analysis. Diabet. Med. 31, 1163-1173 Ramdhani, D. (2014). Buku Ajar Fisiologi Kedokteran edisi 11. Jakarta : EGC Roy, J.L. (2012). Pengaruh Pengelolaan Depresi Dengan Latihan Pernafasan Yoga (Pranayama) Terhadap Perkembangan Proses Penyembuhan Ulkus Diabetikum Di Rumah sakit Pemerintah Aceh. Universitas Indonesia. Safitri, Diana. 2013. Hubungan Antara Tingkat Depresi Dengan Kualitas Hidup Pada Pasien Diabetes Mellitus Tipe II Di Rumah sakit Islam Surakarta. UMS. Semiardji, G. (2013). Stres Emosional Pada Penyandang Diabetes dalam: Soegondo, S., Soewondo, P., Subekti, I., Editor. Penatalaksanaan Diabetes Melitus Terpadu. Jakarta: FKUI. pp 337-346. Septian, A. (2010). Peran Faktor-faktor Psikologis Terhadap Depresi Pada Pasien Diabetes Mellitus Tipe 2 Vol. 41 No.1. UGM. Setyani, Tutut. 2012. Hubungan Tingkat Depresi dengan Kadar Gula Darah Pada Penderita Diabetes Mellitus Tipe II Di Rumah Sakit Umum Daerah Karanganyar. FK UMS. Setyoningrum Irma Astuti, Yunie Armiyati, Rahayu Astuti. (2013). Tingkat Depresi Berdasarkan Derajat Ulkus Diabetes Mellitus Yang Berobat di RSUD kota semarang Siregar, Sofyan. (2011). Statistika Deskriptif Untuk Penelitian.